The relationship between high school English learners’ anxiety and their smartphone addiction: evidence from a daily diary approach - Zhang, Chengli; Han, Ying; Li, Bingqiang; Wang, Jing (Frontiers in Psychiatry, 2025)
BackgroundThe issue of smartphone addiction among high school English learners is becoming more and more significant in this era of information technology, and it is directly associated with their anxiety.MethodsTo examine the correlation between high school English learners’ anxiety level and the severity of smartphone addiction, the anxiety and smartphone addiction levels of high school English learners were explored. SPSS 26 and MPLUS 8.3 were utilized for data analysis. The sample selected by stratified random sampling comprised 248 high school English learners from a high school in Shanxi Province, and a diary survey was conducted for seven consecutive days, obtaining a total of 1,610 valid data points.ResultsThe findings of the multilevel regression model indicated a substantial correlation between anxiety level and the severity of smartphone addiction among high school English learners. Anxiety level was a substantial favorable indicator of the severity of smartphone addiction; a notable disparity existed in the smartphone addiction levels of males and females; however, no significant difference was observed between the genders regarding the predicted influence of anxiety level on the severity of smartphone addiction.ConclusionsThis study examined the effect of anxiety levels on the severity of smartphone addiction and analyzed whether there were gender differences. Based on the results, this study proposes a study on anxiety and smartphone addiction interventions for high school English learners in basic education. The proposal offers evidence from both empirical and theory-based investigations to substantiate the healthy development of high school English learners.